Seasonal variation in the behavior of captive alpine musk deer, Moschus sifanicus, in Xinglongshan Musk Deer Farm, of China - Luan Xiaofeng; Zhao Changjie; Hui Cenyi; Meng Xiuxiang (Zoologia (Curitiba), 2010)
Musk deer farming has the potential to be an effective conservation tool for the protection of musk deer as well as the production of valuable musk. To be successful, this requires a thorough understanding of the behavior of captive musk deer in order to improve their reproductive success and management. Between August 2005 to January 2006, the behavior sampling of 19 male and 13 female captive alpine musk deer, Moschus sifanicus Büchner, 1891, was used to examine the durations of twelve behavioral characteristics during the pre-rut (August to October) and rut seasons (November to January). Both males and females exhibited some seasonal variation in behavior. Males rested and fed more during the pre-rut than the rut and spent more time walking, fighting, and standing alert during the rut. Females spent more time feeding, ruminating, and interacting non-aggressively with other individuals during the pre-rut and more time in agonistic interactions during the rut. The significance of these behavioral changes and their association with husbandry practices and farm management are discussed.